The Economics of Dairy Production - Kövesdi, Gréta Mária; Lakner, Zoltán; Mezőszentgyörgyi, Dávid (Acta Carolus Robertus, 2025)
Farm profitability is influenced by financial, real estate, macroeconomic variables, and industry-specific factors. Gross profit in dairy farming, determined by marketed milk and variable costs, reflects the difference between milk revenue and production costs. Effective management requires continuous assessment of each animal's performance to improve herd productivity and economic efficiency. Benchmarks are essential for decision-making and project management, significantly impacting profitability. Farmers can increase profitability by reducing costs or boosting milk production, requiring thorough economic analysis. Effective strategies include cost minimization, asset utilization, milk marketing, and production expansion. Larger farms benefit from economies of scale, while small farmers must innovate to remain competitive. Net profit, or profit per cow, is a key profitability metric. Effective feeding management and constant awareness of feed and milk prices are crucial. Tracking gross milk income and feed costs provides a more accurate measure of profitability. Various metrics like accounting profit, net farm income, and return on assets (ROA) offer insights into farm financial success, with ROA being useful for comparing different-sized farms. Dairy farm profitability relies on a multifaceted approach, including animal performance monitoring, cost management, and market responsiveness. Leveraging technological advancements and efficient management practices enhances profitability and ensures sustainability.
Keywords: dairy production; dairy profitability; economics; agricultural economy